2011
DOI: 10.1007/s12011-011-9022-0
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase (GSHPx) Activity in the Liver of Red Deer in Relation to Hepatic Selenium Concentrations, Sex, Body Weight and Season of the Year

Abstract: The purpose of this study was to determine glutathione peroxidase (GSHPx) activity in the liver of red deer in relation to selenium concentrations in the liver, as well as to evaluate changes in GSHPx activity according to sex, body weight and season of the year. Total selenium concentration in the liver of red deer averaged 0.095 ± 0.018 μg/g of wet weight. GSHPx activity in the liver of red deer ranged widely from 4.4 to 45.8 U/g of protein. Females were characterized by higher GSHPx activity compared to mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The mean activity of SOD in females only slightly exceeded that of males, while the activity of Se-GSH-Px was very similar in both sexes. No significant differences were reported in the hepatic activity of GSH-Px in male and female pigs by Balagh et al (2012), nor in red deer by Pilarczyk et al (2011). Significantly higher CAT and Mn-SOD activity was observed by Carrillo et al in the liver of female mice (1992), and considerably higher GSHPx and CAT activity was reported by Wu et al (2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mean activity of SOD in females only slightly exceeded that of males, while the activity of Se-GSH-Px was very similar in both sexes. No significant differences were reported in the hepatic activity of GSH-Px in male and female pigs by Balagh et al (2012), nor in red deer by Pilarczyk et al (2011). Significantly higher CAT and Mn-SOD activity was observed by Carrillo et al in the liver of female mice (1992), and considerably higher GSHPx and CAT activity was reported by Wu et al (2003).…”
Section: Discussionmentioning
confidence: 90%
“…The present study showed that the sex of the animals had no considerable effect on liver selenium concentration. The lack of a relationship between selenium concentration and sex was also found in wild boars by Pilarczyk et al (2010), as well as in red deer from northwestern Poland (Pilarczyk et al, 2011) and in polar bears (Rush et al, 2008), although such a correlation was reported in Norwegian red deer (Vikøren et al, 2005) and in red foxes and mongooses (Millán et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Polish wild boars (Sus scofra) also had higher concentrations in kidney than in liver, with the mean of 172 liver values being 0.190 mg/kg (ww) and with spring values being higher than autumn (Pilarczyk et al 2010). In continued work, Pilarczyk et al (2011b) also demonstrated a correlation between liver Se and GPX activity (r 2 00.73).…”
Section: Europementioning
confidence: 95%
“…Of note, PTR-SeNPs antagonized the APAP-induce hepatotoxicity more effectively in WT mice than Nrf2 KO mice as evidenced by the decreased serum AST and LDH contents and increased hepatic SOD, CAT and GSH levels, as well as improvement in the histopathology of liver tissue. Intriguingly, hepatic GSH-Px activity, depending on Selenium concentration, was not more elevated in WT mice than Nrf2 KO mice, which may be attributable to the direct regulation of PTR-SeNPs [40]. Immunoblotting result showed that PTR-SeNPs pretreatment could further promote Nrf2 nuclear translocation in response to APAP challenge, and upregulated the protein expression of GCLC, GCLM, HO-1 and NQO-1.…”
Section: Discussionmentioning
confidence: 85%